Photoacoustic imaging of live chicken embryo at multiple developmental stages - Sharma, Arunima (2021)
Chicken embryo remains a commonly used model for biomedical research due to its ease of availability, accessibility for surgical manipulations, and biological similarities with humans. Although, it is being extensively used for cancer, cardiovascular, and developmental studies, non-destructive imaging of live embryo vasculature with high optical contrast remains a challenge. In this work, photoacoustic tomography of chicken embryos developing in bioengineered eggshell was performed. Chicken embryos at different developmental stages were irradiated with laser pulses at wavelengths 532 nm and 740 nm to acquire cross sectional images at various depths. We have shown a label free method for imaging of live chicken embryo while maintaining its integrity. We demonstrated that our method has the potential to be a powerful non-invasive imaging method for studying vasculature growth and development in chicken embryos.